Danggui Buxue decoction regulates the immune function and intestinal microbiota of cyclophosphamide induced immunosuppressed mice - Huang, Huan; Xie, Yufei; Li, Xifeng; Gui, Fuxing; Yang, Pingrui; Li, Yutao; Zhang, Li; Du, Hongxu; Bi, Shicheng; Cao, Liting (Frontiers in Pharmacology, 2024)
Ethnopharmacological relevance Danggui Buxue decoction (DBD) is a traditional Chinese herbal formula. According to the theory of traditional Chinese medicine, the combination of Astragali Radix (AR) and Angelica sinensis (AS) is a classic prescription of tonifying qi and enriching blood. DBD has the functions of hematopoietic, immune enhancement and inflammation inhibition, usually used to treat qi and blood deficiency symptoms. Aim of the study Cyclophosphamide (CY) can inhibit humoral and cellular immunity, leading to the overall immune disorder of the body, resulting in immunosuppressive (IS). Pre-laboratory studies confirmed the immunomodulatory effects of DBD, but its mechanisms have not been thoroughly studied. In this study, the main purpose was to determine the effects of DBD on the immune function and intestinal mucosal barrier function of IS mice induced by CY, and initially explored the immunomodulatory mechanism of DBD. Materials and methods 100 g of AR and 20 g of AS were accurately weighed and 0.5 g/mL of the DBD was obtained by boiling, filtration and rotary evaporation. Then, mice in the DBD group were administered 5 g/kg of DBD by gavage, positive group were administered 40 mg/kg of levamisole hydrochloride, whereas those in the control and model groups were given the corresponding volume of normal saline by gavage for 1 week. At the end of the experiment, blood, spleen, thymus, ileum and cecum contents of all the experimental mice were collected aseptically. IS mouse model induced by intraperitoneal injection of 80 mg/kg CY for three consecutive days. Pathomorphology was used to observe the physical barrier of the intestine, flow cytometry to detect splenic lymphocytes, immunohistochemistry to determine the content of intestinal barrier-associated proteins, ELISA to measure the secretion of ileal SIgA, qRT-PCR to detect the mRNA expression of immune-related genes in the intestine, and high-throughput sequencing and analysis of cecum contents. Results DBD alleviated spleen tissue damage and restored impaired immune functions, such as increased thymus index and CD4+/CD8+ subsets of spleen lymphocytes. In addition, DBD could increase ileum villi length and the ratio of villi length to crypt depth (V/C), and decrease crypt depth. Moreover, DBD administration up-regulated the expression of ZO-1, Occludin, Claudin-1, MUC-2 mRNA in ileum. And the secretions of sIgA and ZO-1 in ileum were also significantly improved. Furthermore, the administration of DBD can increase the diversity of gut microbiota, improve the composition of intestinal flora and increase the relative abundance of beneficial genus, such as Bacteroides. Conclusion DBD alleviated CY-induced immune damage by decreasing the ratio of spleen index to CD4+/CD8+ of T lymphocyte subsets. And the intestinal barrier function of mice was by improves improving the intestinal morphology of the ileum and up-regulating the expression levels of ZO-1, MUC-2 and SIgA. DBD regulates CY-induced gut microbiota dysregulation in mice by increasing species diversity and richness, regulating the phylum, class and order levels of Bacteroidetes.